MoA BETWEEN USM AND MALAYSIAN NUCLEAR AGENCY TO ENHANCE STI - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KUALA LUMPUR, 26 October 2015 – The recent signing of a Memorandum of Agreement (MoA) between USM and the Malaysian Nuclear Agency on the occasion of the Technology Preview and Nuclear Showcase Malaysia 2015 programme will strengthen efforts at developing Science, Technology and Innovation (STI).